2005
DOI: 10.4049/jimmunol.175.2.780
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Gene Therapy for Tolerance: B7 Signaling Is Required for Peptide-IgG Gene-Transferred Tolerance Induction

Abstract: LPS-activated B cells, transduced with IgG fusion proteins, are highly tolerogenic APCs. To analyze the mechanisms for this B cell-delivered gene therapy, we first followed the fate of CFSE-labeled B cell blasts. These cells primarily localized to the spleen, where a small population persisted for at least 1 mo after injection. By day 7 after injection, ∼95% of the transduced cells had divided at least once, presumably an effect of the in vitro LPS activation into the cycle, because resting cells did not divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…In addition, MZ B cells also express higher levels of B7.1 and B7.2 than FO B cells do, thus facilitating effective antigen presentation to CTLA-4 ϩ regulatory T cells. 23,24 Through fluorescence-activated cell sorter analysis, we found that the B7 costimulatory molecules were further up-regulated on IgG1 anti-CD20 treatment plus high-dose FVIII exposure. In contrast, control IgG plus FVIII treatment had no significant effect on this phenotype of MZ B cells, compared with nontreated naive mice (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MZ B cells also express higher levels of B7.1 and B7.2 than FO B cells do, thus facilitating effective antigen presentation to CTLA-4 ϩ regulatory T cells. 23,24 Through fluorescence-activated cell sorter analysis, we found that the B7 costimulatory molecules were further up-regulated on IgG1 anti-CD20 treatment plus high-dose FVIII exposure. In contrast, control IgG plus FVIII treatment had no significant effect on this phenotype of MZ B cells, compared with nontreated naive mice (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we have performed experiments in which the B cells of B MOG mice were activated in vivo using LPS or anti-CD40, but naive T cells transferred to these mice were not sufficiently stimulated to proliferate. It has previously been shown that activated transferred B cells need to express B7 molecules to induce tolerance (10). It is possible that, in our system, tolerance can also be achieved by costimulatory molecules other than B7.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, memory T cells may not need costimulation and could therefore be activated by B cells. A problem of this hypothesis is that also activated B cells, which normally do express B7 molecules, can induce tolerance of T cells (10). It is therefore not clear whether it is indeed the absence of costimulation what causes B cells to induce tolerance.…”
mentioning
confidence: 98%
“…Though the number of B cells used to induce tolerance was relatively high, it is unlikely that this contributed to an specific effect, because control mice injected with an equal number of nontransduced or GFP-transduced B cells showed no induction of an immune response. Moreover, in earlier studies performed by others (27,28), a comparable number of B cells (15-20 ϫ 10 6 ) were transferred to confer Ag-specific immune response.…”
Section: Discussionmentioning
confidence: 99%